The Relationship between Hyponymy, Polysemy, and Redundancy in Kompas.com News: - Agus Wanto (Raja Zulkarnain Education Foundation, 2025)
This study aims to describe the semantic relationships between hyponymy, polysemy, and redundancy found in the online news text of Kompas.com entitled “Food Fortification, an Effective Strategy for Achieving Superior Human Resources and National Nutritional Security” published in the November 2025 edition. This study used a qualitative descriptive method, with data in the form of words, phrases, clauses, and sentences containing these semantic relationships. Data collection techniques were conducted using reading and note-taking, while data analysis used content analysis, focusing on the meaning and semantic relationships within the news text. The results show that various forms of semantic relationships enrich the lexical structure of the news, including hyponymy in the terms food and nutrition, polysemy in words with more than one meaning depending on the context, and redundancy found in the form of repeated words and phrases. Overall, the use of these semantic relationships demonstrates the linguistic function of clarifying messages, emphasizing meaning, and maintaining effective communication in online news texts.